ANALISIS KOMITMEN PROFESIONAL DAN SOSIALISASI ANTISIPATIF SERTA HUBUNGANNYA DENGAN WHISTLEBLOWING - Bakri, Bakri (IAIN Sultan Amai Gorontalo, 2014)
Accounting profession experienced a crisis of confidence as much a failure of ethics . Because it emphasized the importance of professionals in improving ethical behavior from the start of their career started , even before they enter the profession. This research is aimed at behavioral accounting research to examine differences in the level of professional commitment and anticipatory socialization ( proxied by financial reporting ) as well as its relationship with the perception of the importance of whistleblowing which includes whistleblowing and whistleblowing intention them .The method used in this research was a survey of students . This study used a sample of university accounting students Loulembah Gorontalo . To examine the relationship of professional commitment and anticipatory socialization to the whistleblowing used regression test . Meanwhile, to see how the level of professional commitment and anticipatory socialization and perceptions of the importance of whistleblowing and whistleblowing intention among accounting students used simultaneously and partial test of each variable .The results showed that there is a relationship between professional commitment and anticipatory socialization to whistleblowing . And of the partial test results obtained that all the variables that have significant differences .